The roles of independent children's rights institutions in advancing human rights of children - Lux, Agnes; Gran, Brian (Sociological studies of children and youth ;, 2022)
Independent children's rights institutions (ICRIs) have been established across the world. Endorsed by the UN, they are independent of their governments and endowed with legal powers. Yet we know little about how ICRIs function. How do they work? What impacts their success? What objectives do ICRIs seek to achieve? The contributors to this edited collection provide first-hand experiences in directing, working for, and studying ICRIs and detail their unique, in-depth accounts of factors shaping ICRIs' efforts to monitor and advance children's rights. Chapters examine ICRIs in Belgium, Germany, Hungary, Ireland, the Netherlands, Pakistan, and the United States, as well as an extraordinary network of ICRIs, and introduce innovative ideas of how to think about ICRIs' independence and legal powers. Offering perspectives from across the world, this volume provides both theoretical and practical insights on a crucial element of children's rights, independent children's rights institutions. The Roles of Independent Children's Rights Institutions in Advancing Human Rights of Children is essential reading for students, researchers, and scholars interested in studies of sociology of childhood, law and society, children's rights, and human rights.